Following hushtag (#)MOOC: Mobility of online courses on twitter - Enriquez-Gibson, Judith (Proceedings of the International Conference on Networked Learning, 2014)
Electronic posts in social media sites have led to an interpersonal shift that allows discourse-search through the use of hashtags resulting in the emergence of ‘searchable talk' (Zappanigna, 2011) and the rise of database culture (Miller, 2008). The hashtags have referred to ‘trending topics' and have become linguistic markers for ‘findability' towards a new form of sociality that is not based on reciprocity or notion of virtual community. What connects users is not who or an ego-centric node, but what is pass along in a ‘stream' (ie. the movement of ideas, information and sentiments) of re-tweets (RT's) and mentions (@) about some hashtagged (#) topics. This streaming sociality is the focus of this paper. To understand streaming sociality as an opportunity to expand social science research, this paper focuses on small talk about ‘massive' and trendy topics on education-related ideas and initiatives, namely, mooc, coursera and futurelearn, on Twitter. First, it examines how Twitter as a social technology could be performed differently in simultaneous ways as context, tool and data set of social science research. At the level of theory, a ‘new' form of networked sociality is considered outside the ‘big data' slogan and extreme reactions on topics related to particular political events, campaigns, disasters, disease outbreaks, brand marketing or self-promotion. Then, this paper asks how the streaming sociality of Twitter may transform the content, movement and geographical trends of online courses associated with #coursera and #futurelearn by tagging and performing the circulation of a different kind of mooc - mobility of online courses ((#)mooc). It will venture into unfamiliar territories and spaces mostly at an interface hoping to follow (#)mooc through hashtags, re-tweets and mentions of education-related tweets. At the point of data collection and analysis, free trial versions of social media analytics and visualisation softwares are used to attempt an alternative way of following the movement of online courses without ‘going big' or ‘being massive'. To follow and tag what is happening to online courses through the ‘code/space' (Kitchen & Dodge, 2011) of Twitter, it is necessary to attend to ‘hushtag' bondings. ‘Hushtag' refers to all those posts or news and events not explicitly tagged or mentioned by users. These muted tags give room for analytical moves that could potentially bridge the methodological divide between qualitative and quantitative epistemologies as social science researchers are confronted with the power of algorithms and monumentally detailed by-product data (Beer, 2012).